Efficacy of decision aid delivery modes in prostate cancer screening: umbrella review and network meta‐analysis - Ang, Zen Yang; Kong, Yuke‐Lin; Md Nesran, Zarith Nameyrra; Lee, Shaun Wen Huey (BJU international, 2025)
Objective To review and compare the efficacy of different delivery modes of decision aids (DAs), including computer‐based, print‐based, multimedia‐based, video‐based, and website‐based on decision‐making outcomes for prostate cancer screening compared to usual care (UC) and among the delivery modes. Methods PubMed, the Excerpta Medica dataBASE (EMBASE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Google Advanced Search, and Turning Research Into Practice (TRIP) Database were systematically searched from inception to August 2023. The primary outcomes were knowledge level, knowledge scores, participation in shared decision‐making (SDM), decisional conflict, and preference for SDM participation. Secondary outcomes were the proportion of subjects who underwent screening (actual screening utilisation) and the proportion of subjects who intended to be screened (intention to undergo screening). Network and pairwise meta‐analyses were performed using random‐effects models. Results Seven systematic reviews were included. Network meta‐analysis found that multimedia (relative risk [RR] 1.51, 95% confidence interval [CI] 1.02–2.24), print (RR 1.82, 95% CI 1.23–2.69), and website‐based (RR 1.99, 95% CI 1.32–3.01) DAs significantly increased participation in SDM compared to the computer‐based DA. There was a significant reduction in the actual screening utilisation in the computer DA arm compared to the other delivery modes. No significant differences between all delivery modes were noted on knowledge levels, knowledge scores, decisional conflict, preference for SDM participation, and intention to undergo screening. The highest mean surface under the cumulative ranking curve for all primary outcomes showed that website‐based was the most effective delivery mode, followed by print‐based DA. The pairwise meta‐analysis showed a significant increase in participants’ knowledge level, knowledge scores, a reduced intention to undergo screening and actual screening utilisation compared to UC. Conclusions The findings suggest that different types of DAs have varying levels of effectiveness in increasing knowledge level, knowledge scores, participation in SDM, and influencing screening behaviours. While website‐based DA appeared the most effective, employing the print‐based DA could be a practical solution in settings with limited resources.